UMPSA solicitude for Felda Rentam citizens in the TVET Promotion Mission in Bera - Naqiah, Puaad (UMPSA, 2024)
BERA, 27 July 2024 - Volunteers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), comprising 20 staff members and 14 students, participated in the ‘Ziarah Prihatin’ Programme to local residents in Felda Rentam recently.